Type 2 Diabetes in Youth - Goutham Rao MD; Elizabeth T. Jensen PhD (SAGE Publishing, 2020)
The incidence of type 2 diabetes in children and adolescents in the United States rose at an annual rate of 4.8% between 2002-2003 and 2014-2015. Type 2 diabetes progresses more aggressively to complications than type 1 diabetes. For example, in one large epidemiological study, proliferative retinopathy affected 5.6% and 9.1% of children with type 1 and type 2 diabetes, respectively. Screening begins at age 10 or at onset of puberty, and is recommended among children with a BMI% ≥85 with risk factors such as a family history and belonging to a high risk racial or ethnic or racial group. HbA1C% is preferred for screening as it does not require fasting. As distinguishing between type 1 and type 2 diabetes is not straightforward, all children with new onset disease should undergo autoantibody testing. Results of lifestyle interventions for control of type 2 diabetes have been disappointing, but are still recommended for their educational value and the potential impact upon some participants. There is limited evidence for the benefit of newer mediations. Liraglutide, a GLP-1 agonist, however, has been shown to significantly reduce HbA1C% in one study and is now approved for children. Liraglutide should be considered as second line therapy.